SYNTHESIS AND BIOLOGICAL APPLICATIONS OF SOME NOVEL SCHIFF BASE TRANSITION METAL (II) COMPLEXES DERIVED FROM THIOPHENE-2- CARBOXALDEHYDE AND 4, 4’ DIAMINO DIPHENYL METHANE (International Journal of Food and Nutritional Sciences, 2022)
Schiff bases are considered as privileged ligand in coordination chemistry as they easily form stablecomplexes with most transition metal complexes. In this paper, a novel Schiff base ligand derived fromThiophene-2-carboxaldehyde (TPC) and 4,4’ diamino diphenyl methane (DDM) and its transition metalcomplexes Cu(II), Zn(II), Co(II) and Ni(II). Antimicrobial, antioxidant, anti-inflammatory, larvicidal, DNAcleavage activity against standard at variable concentrations revealed that the Cu(II), Zn(II), Co(II) and Ni(II)complexes show enhanced antimicrobial, free radical scavenging and anti-inflammatory activities ascompared to TPC and DDM.